Determinants of attitudes towards professional mental health care, informal help and self-reliance in people with subclinical depression. (February 2016) - van Zoonen, Kim; Kleiboer, Annet; Cuijpers, Pim; Smit, Jan; Penninx, Brenda; Verhaak, Peter; Beekman, Aartjan
Background: Although little is known about which people with subclinical depression should receive care to prevent the onset of depression, it is clear that remediating symptoms of depression is important. However, depending on the beliefs people hold about help, some people will seek professional help, while others seek informal help or solve problems on their own. Aims: This study examined associations between attitudes about help and socio-demographic variables, mastery, severity of depressive symptoms, accessibility to care, and health care utilization at baseline and 4-year follow-up. Methods: Data were derived from a large cohort study, the Netherlands Study of Depression and Anxiety (NESDA). A total of 235 respondents with subclinical depression completed questionnaires at baseline and follow-up. Attitude was assessed using a short version of the 'Trust in mental health care' questionnaire. Results: Positive attitude towards professional care was associated with being male, younger age, higher mastery and easy accessibility to care. Positive attitude towards informal help was associated with higher mastery and unemployment. Older age, less accessibility to care and lower mastery were associated with positive attitude towards self-reliance. A change in care utilization was associated with positive attitudes towards professional care at follow-up. Conclusions: People differ in the way they cope with symptoms which may influence their preferred care. Higher levels of mastery were positively associated with professional and informal care, but negatively associated with self-reliance. Both age and mastery showed relatively large effect sizes.